2017
DOI: 10.3390/jcdd4030010
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterases 3 and 4 Differentially Regulate the Funny Current, If, in Mouse Sinoatrial Node Myocytes

Abstract: Cardiac pacemaking, at rest and during the sympathetic fight-or-flight response, depends on cAMP (3′,5′-cyclic adenosine monophosphate) signaling in sinoatrial node myocytes (SAMs). The cardiac “funny current” (If) is among the cAMP-sensitive effectors that drive pacemaking in SAMs. If is produced by hyperpolarization-activated, cyclic nucleotide-sensitive (HCN) channels. Voltage-dependent gating of HCN channels is potentiated by cAMP, which acts either by binding directly to the channels or by activating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
(88 reference statements)
2
11
0
Order By: Relevance
“…The authors demonstrated that PDE4 inhibition in mouse SANCs produced a PKA-independent depolarizing shift in the V 1/2 of I f at rest, likely via a direct binding of elevated cAMP to the channel, but did not remove the requirement for PKA in β 2 AR-to-HCN signaling. In contrast, PDE3 inhibition produced PKA-dependent changes in I f both at rest and in response to β 2 AR stimulation ( St Clair et al, 2017 ). Microdomain-specific localization and activity of PDEs in SANCs have been recently reviewed by Vinogradova et al (2018) and highlight functional importance of local cAMP microdomains with high and low cAMP levels which are involved in local regulation of coupled-clock system components.…”
Section: Membrane Clockmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated that PDE4 inhibition in mouse SANCs produced a PKA-independent depolarizing shift in the V 1/2 of I f at rest, likely via a direct binding of elevated cAMP to the channel, but did not remove the requirement for PKA in β 2 AR-to-HCN signaling. In contrast, PDE3 inhibition produced PKA-dependent changes in I f both at rest and in response to β 2 AR stimulation ( St Clair et al, 2017 ). Microdomain-specific localization and activity of PDEs in SANCs have been recently reviewed by Vinogradova et al (2018) and highlight functional importance of local cAMP microdomains with high and low cAMP levels which are involved in local regulation of coupled-clock system components.…”
Section: Membrane Clockmentioning
confidence: 99%
“…Though such simplification was beneficial for computational modeling and enabled the development of relatively straightforward biophysical models based on non-linear dynamics and oscillatory theory, it recently became evident that this simple “random collision model” is inadequate to explain the emerging experimental results which highlight microdomain-specific regulation of cardiomyocyte physiology (reviewed in details elsewhere, Zaccolo and Pozzan, 2002 ; Warrier et al, 2007 ; Best and Kamp, 2012 ; Balycheva et al, 2015 ; Vinogradova et al, 2018 ). In the SAN, these include findings on a complex spatial-temporal coupling between the membrane- and Ca 2+ clocks confirmed in various species, including human ( Kim et al, 2018 ; Tsutsui et al, 2018 ), synchronization of spontaneous LCRs between discrete RyR clusters ( Stern et al, 2014 ; Torrente et al, 2016 ), compartmentalized autonomic regulation of pacemaker ion channels which relies on tightly confined cAMP signaling ( Barbuti et al, 2004 ; St Clair et al, 2017 ; Vinogradova et al, 2018 ), as well as microdomain-specific remodeling of ion channels secondary to structural alterations including changes in scaffolding proteins ( Le Scouarnec et al, 2008 ; Alcalay et al, 2013 ; Bryant et al, 2018 ). The emerging results demonstrate that the functioning of the complex pacemaking machinery at the cellular level depends on tightly regulated spatiotemporal signals which are restricted to precise subcellular microdomains and associated with discrete clusters of different ion channels, transporters and regulatory receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Because so many of the neurohumoral pathways in the SAN activate AC and GC, without intracellular control these secondary messenger systems would be limited in their ability to specifically target a response (Fischmeister et al, 2006). In mouse SAN myocytes it has been shown that compartmentalization of HCN channels by PDEs may play an important role in regulating β 1 -AR modulation of I f (St. Clair et al, 2017) . Specifically, it appears that PDE4 acts as a barrier that isolates HCN channels from the rest of the cell, so that under basal conditions they cannot be accessed by cAMP, and that PDE3 interacts with PKA to favor the β 1 -AR/cAMP/PKA/HCN pathway (rather than activation by direct binding of cAMP to HCN) (St. Clair et al, 2017).…”
Section: Intracellular Compartmentalizationmentioning
confidence: 99%
“…Other ionic currents involved in the generation of DD are also regulated by PDEs, e.g., inhibition of PDE3 in rabbit SANC increases I K and shifts voltage dependence of I f activation to more positive potentials ( DiFrancesco and Tortora, 1991 ; Hata et al, 1998 ; Vinogradova et al, 2008 ). In mouse SANC, inhibition of PDE activity by IBMX or PDE4 activity by rolopram shifts voltage dependence of I f current to more positive potentials ( St Clair et al, 2017 ). The PDE3 inhibitor, milrinone, significantly increases I f current amplitude by ∼20% ( Springer et al, 2012 ) without shift of the voltage dependence of I f current ( St Clair et al, 2017 ).…”
Section: Effects Of Pde Inhibition On Ionic Currents and Sr Ca mentioning
confidence: 99%
“…In mouse SANC, inhibition of PDE activity by IBMX or PDE4 activity by rolopram shifts voltage dependence of I f current to more positive potentials ( St Clair et al, 2017 ). The PDE3 inhibitor, milrinone, significantly increases I f current amplitude by ∼20% ( Springer et al, 2012 ) without shift of the voltage dependence of I f current ( St Clair et al, 2017 ).…”
Section: Effects Of Pde Inhibition On Ionic Currents and Sr Ca mentioning
confidence: 99%